Dendritic self-avoidance - Soba, Peter (Springer Japan, 2016)
Self-avoidance allows a neuron’s dendrites to recognize and repel each other. It constitutes one of the basic mechanisms facilitating even patterning of the receptive field. Self-avoidance enables neurons to distinguish self- from nonself-dendrites in complex systems so their receptive fields can coexist in overlapping territories. The phenomenon was first described in leech and later in Drosophila and C. elegans, with recent studies in vertebrate systems revealing self-avoidance as a universally conserved mechanism required to pattern dendrites of many if not all neurons. Molecularly, members of the immunoglobulin superfamily (IgSF), in particular Down’s syndrome cell adhesion molecule (Dscam), and clustered protocadherins (Pcdhs) play a prominent role in mediating self-avoidance. Here, I will summarize the findings and advances in our understanding of the conceptual and molecular nature of dendrite self-avoidance from the cellular to organismal level and discuss its contribution to dendritic patterning.
CRIS-Team Scopus Importer:2021-11-16
Keywords: Clustered protocadherins (Pcdhs); Dendrite repulsion; Dendritic self-avoidance; Down’s syndrome cell adhesion molecule (Dscam); Homotypic interaction